Neuroprotective Effect of Nerve Growth Factor Loaded in Porous Silicon Nanostructures in an Alzheimer's Disease Model and Potential Delivery to the Brain. Issue 45 (4th September 2019) - Zilony‐Hanin, Neta; Rosenberg, Michal; Richman, Michal; Yehuda, Ronen; Schori, Hadas; Motiei, Menachem; Rahimipour, Shai; Groisman, Alexander; Segal, Ester; Shefi, Orit
Abstract: Nerve growth factor (NGF) plays a vital role in reducing the loss of cholinergic neurons in Alzheimer's disease (AD). However, its delivery to the brain remains a challenge. Herein, NGF is loaded into degradable oxidized porous silicon (PSiO2 ) carriers, which are designed to carry and continuously release the protein over a 1 month period. The released NGF exhibits a substantial neuroprotective effect in differentiated rat pheochromocytoma PC12 cells against amyloid‐beta (Aβ)‐induced cytotoxicity, which is associated with Alzheimer's disease. Next, two potential localized administration routes of the porous carriers into murine brain are investigated: implantation of PSiO2 chips above the dura mater, and biolistic bombardment of PSiO2 microparticles through an opening in the skull using a pneumatic gene gun. The PSiO2 ‐implanted mice are monitored for a period of 8 weeks and no inflammation or adverse effects are observed. Subsequently, a successful biolistic delivery of these highly porous microparticles into a live‐mouse brain is demonstrated for the first time. The bombarded microparticles are observed to penetrate the brain and reach a depth of 150 µm. These results pave the way for using degradable PSiO2 carriers as potential localized delivery systems for NGF to the brain. Abstract : Nerve growth factor (NGF) is a promising neuroprotective drug for Alzheimer's disease, however, its delivery to the brain remains a challenge. NGF is incorporated in degradable porous silicon carriers, showing a continuous, sustained, and effective release for over a month. Toward clinical use, the administration of the carriers to murine brain by either direct implantation or biolistically is demonstrated.